Neutral aqueous zinc air / iodine hybrid battery and electrolyte and positive electrode thereof

By using neutral aqueous electrolyte and porous carbon positive electrode material loaded with FeN particles in zinc empty/iodine hybrid batteries, the problems of disproportionation reaction and carbonate blockage in alkaline media are solved, and high under neutral conditions are achieved The performance of zinc-air/iodine hybrid batteries is improved by a longer cycle life.

CN119275442APending Publication Date: 2025-01-07ZHEJIANG FORESTRY UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411358282.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When existing zinc-vacuum/iodine hybrid batteries are run in alkaline media, the intermediate product I2 generated during charging is spontaneously disproportionate, resulting in a significant reduction in the actual capacity of the battery, and the alkaline electrolyte reacts with carbon dioxide in the air to form insoluble carbon. The acid salt blocks the positive electrode, affecting the stability and energy density of the battery.

Method used

Using neutral water-based zinc-vacuo/iodine hybrid battery electrolyte and porous carbon positive electrode material with FeN particles is used to regulate the concentration of zinc ions, iodine ions and conductive additives, and formed by high-temperature calcination bimetallic and aminoantipirine Metal organic framework structure realizes reversible and stable transformation of oxygen species and iodine species under neutral conditions.

Benefits of technology

The reversible and stable conversion of oxygen species and iodine species under neutral conditions has been achieved, the specific capacity and circulation stability have been improved, the ultra-long cycle life and high specific energy density have a wide range of raw materials, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275442A_ABST
    Figure CN119275442A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte of a neutral aqueous zinc air / iodine hybrid battery, which is a neutral electrolyte and comprises a zinc source, an iodine source and a conductive additive. The invention also discloses a positive electrode of the neutral aqueous zinc air / iodine hybrid battery, and the positive electrode is a FeN particle-loaded porous carbon positive electrode material obtained by calcining a metal organic framework formed by bimetallic (Fe, Zn) and aminoantipyrine at a high temperature. The invention also discloses a neutral aqueous zinc air / iodine hybrid battery comprising the neutral electrolyte and a porous carbon positive electrode material loaded with FeN particles. The neutral aqueous zinc air / iodine hybrid battery constructed by the electrolyte and the positive electrode provided by the invention realizes reversible and stable conversion of oxygen species and iodine species under a neutral condition, and has excellent specific capacity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc-air battery energy storage devices, and in particular relates to a neutral water system zinc-air / iodine hybrid battery and an electrolyte and a positive electrode thereof. Background Art

[0002] Zinc-air batteries have high theoretical energy density, low cost of zinc negative electrode, safety and environmental protection, and have good application prospects. However, the rechargeability of zinc-air batteries is poor, especially the charging voltage is too high, which often causes the catalyst to be oxidized and deactivated. Therefore, it is still a huge challenge to achieve practical application. Zinc-air / iodine hybrid batteries introduce iodine ions into the electrolyte to undergo iodine oxidation reaction (IOR) to replace oxygen evolution reaction (OER), thereby significantly reducing the charging voltage and improving energy efficiency. The introduction of soluble iodide ions not only accelerates the reaction kinetics and adjusts the solvation structure of zinc ions, but also inhibits the formation of dendrites. However, almost all reported zinc-air / iodine hybrid batteries operate in alkaline media, and the intermediate product I2 produced during the charging process will spontaneously undergo disproportionation reaction to form stable IO3 - At the same time, alkaline electrolytes easily react with carbon dioxide in the air to form insoluble carbonates, which irreversibly consume the electrolyte and physically block and chemically deactivate the porous air cathode, resulting in a significant reduction in the actual capacity of the battery. Therefore, the development of zinc-air / iodine hybrid batteries that can operate stably under neutral conditions is the key to achieving high specific energy and high stability of the battery.

[0003] In order to make neutral zinc-air / iodine hybrid batteries a truly competitive alternative energy storage system, several key issues need to be addressed. First, new neutral or near-neutral electrolyte systems need to be developed to suppress the disproportionation reaction of iodide and promote the efficient reduction of iodate. Second, the design of electrode materials should be optimized to improve their catalytic activity and stability under neutral conditions. In addition, the charging and discharging mechanism of ZAIBs needs to be studied in depth to better control the operation of the battery and optimize its performance. Inspired by this, "Angewandte Chemie" (2023, Vol. 62, Page 202303845) publicly reported an organic zinc-air / iodine hybrid battery mediated by reversible I3- / I- redox, demonstrating improved cycle efficiency (56.03% at 0.4mA cm-2) and long cycle time. However, due to the low ionic conductivity of organic electrolytes, the energy density and power density of such ZAIBs may be limited. The ionic conductivity of aqueous solutions is higher than that of organic electrolytes, which is conducive to achieving better battery performance. However, there is an urgent need to develop methods to effectively regulate and realize high-energy, efficient and reversible iodine conversion electrochemical processes under simple conditions to enhance the performance of neutral zinc-air / iodine hybrid batteries. Summary of the invention

[0004] The object of the present invention is to provide a neutral aqueous zinc-air / iodine hybrid battery and its electrolyte and positive electrode. The neutral aqueous zinc-air / iodine hybrid battery constructed by the electrolyte and positive electrode provided by the present invention realizes the reversible and stable conversion of oxygen species and iodine species under neutral conditions, and has excellent specific capacity and cycle stability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme:

[0006] The invention discloses an electrolyte for a neutral aqueous zinc-air / iodine hybrid battery. The electrolyte is a neutral electrolyte and comprises a zinc source, an iodine source and a conductive additive.

[0007] The zinc source is from one of zinc sulfate, zinc acetate or zinc oxide.

[0008] The iodine source is selected from one or a combination of at least two of potassium iodide, sodium iodide, potassium iodate or elemental iodine.

[0009] The conductive additive is selected from one or a combination of at least two of potassium acetate, sodium chloride, potassium chloride, sodium sulfate or potassium sulfate.

[0010] The molar concentration of zinc ions in the zinc-air / iodine hybrid battery electrolyte is 0.1M-3M, the molar concentration of iodine ions is 0.1M-3M, and the molar concentration of the conductive additive is 0.1M-3M.

[0011] The composition and concentration of the zinc-air / iodine hybrid battery electrolyte provided by the present invention affect the conductivity and reaction activity. Preferably, the molar concentration of zinc ions in the zinc-air / iodine hybrid battery electrolyte is 1M to 3M, the molar ratio of iodine ions is 1M to 2M, and the molar concentration of the conductive additive is 1M; the above-mentioned limitation is more conducive to improving the energy conversion efficiency and cycle stability of the battery.

[0012] The present invention also provides a positive electrode for a neutral water system zinc-air / iodine hybrid battery, wherein the positive electrode is a porous carbon positive electrode material loaded with FeN particles obtained by high-temperature calcination of a metal organic framework formed by bimetallic (Fe, Zn) and aminoantipyrine.

[0013] The preparation method of the porous carbon positive electrode material loaded with FeN particles comprises:

[0014] (1) dispersing 0.1-0.5 g of silica nanospheres, 0.5-1 g of 4-aminoantipyrine, 0.01-0.5 g of ferric nitrate nonahydrate and 0.1-0.5 g of zinc nitrate hexahydrate in methanol, and heating until the methanol evaporates to obtain a solid powder;

[0015] (2) heating the solid powder to 600-1000° C. in an inert atmosphere and maintaining the temperature for 1-3 hours, and removing the silica nanospheres with an alkaline solution;

[0016] (3) The product of step (2) is heated to 800-1000° C. and heat treated for 2-4 hours to obtain a porous carbon positive electrode material loaded with FeN particles.

[0017] The present invention regulates the number of active sites by regulating the feeding amount of step (1), and regulates the physical phase of the final substance by regulating the heating temperature of step (2).

[0018] Preferably, heating to 900-1000° C. in step (2) is more conducive to improving the energy conversion efficiency and cycle stability of the battery.

[0019] Further preferably, the feeding amount of step (1) is 0.3 g of silica nanospheres, 0.6 g of 4-aminoantipyrine, 0.1 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.3 g of zinc nitrate hexahydrate, and the heating temperature in step (2) is 900°C and the heat treatment is performed for 1 hour.

[0020] In step (1), the preparation method of the silica nanospheres is as follows: 50 to 100 ml of anhydrous ethanol, 10 to 20 ml of deionized water and 1 to 5 ml of tetraethoxysilane are mixed, 2 to 6 ml of ammonia water is added dropwise, and the silica nanospheres are obtained by centrifugation; in step (2), 1 to 6 M potassium hydroxide solution is used for washing at 80° C. for 24 to 48 hours to remove the silica nanospheres.

[0021] In step (3), the porous carbon positive electrode material loaded with FeN particles has a loading amount of 0.4-1 wt% of FeN particles, a particle size of 20-50 nm, a pore size of 0.5-10 nm of porous carbon, and a surface area of ​​300-600 m 2 g -1 .

[0023] The present invention also provides a neutral aqueous zinc-air / iodine hybrid battery, the battery comprising the above neutral electrolyte, a porous carbon positive electrode material loaded with FeN particles, and a zinc sheet negative electrode.

[0024] Preferably, the porous carbon positive electrode material loaded with FeN particles is used as a neutral water system zinc-air / iodine hybrid battery air positive electrode: the positive electrode material, polytetrafluoroethylene and conductive carbon black are weighed, ground evenly in a mass ratio of 8:1:1, and N-methylpyrrolidine is added to obtain a slurry, and then the slurry is evenly coated on a foam nickel current collector, and the neutral water system zinc-air / iodine hybrid battery air positive electrode is obtained after drying.

[0025] When the battery is working, the positive electrode material of the neutral aqueous zinc-air / iodine hybrid battery realizes normal charge and discharge through oxygen reduction and oxygen evolution reactions. At the same time, the positive electrode material can also realize I at a smaller charge and discharge voltage.- / I3 - The neutral zinc-air / iodine hybrid battery constructed by the present invention realizes the reversible and stable conversion of oxygen species and iodine species under neutral conditions through the coordinated regulation of electrodes and electrolytes, and thus has excellent specific capacity and cycle stability.

[0026] Compared with the prior art, the present invention has the following excellent effects: the present invention realizes a neutral aqueous zinc-air / iodine hybrid battery with high reversibility and high specific energy through iodine conversion electrochemistry: the porous carbon positive electrode material loaded with FeN particles is characterized by FeN cluster active sites and honeycomb porous structure, and performs well in oxygen reduction reaction, oxygen precipitation reaction, iodine reduction reaction and iodine precipitation reaction; the neutral aqueous iodine solution realizes the high reversibility of iodine species during the charge and discharge process. Thanks to the extremely low charging voltage, the neutral aqueous zinc-air / iodine hybrid battery provided by the present invention optimally realizes an ultra-long cycle life of up to 1900 hours and a high specific energy of 665mAh / g. In addition, the main raw materials used in the present invention are widely available, low-cost and environmentally friendly, simple to operate, safe and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a working mechanism diagram of the neutral water system zinc-air / iodine hybrid battery provided by the present invention.

[0028] Figure 2 This is a morphology of the porous carbon cathode material loaded with FeN particles prepared in Example 1 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0029] Figure 3 This is the XRD spectrum of the porous carbon cathode material loaded with FeN particles prepared in Example 1 measured by a D8 X-ray diffractometer of Bruker Corporation, USA, wherein: the abscissa X is the diffraction angle (2θ), and the ordinate Y is the relative diffraction intensity.

[0030] Figure 4 This is a transmission morphology image of the porous carbon cathode material loaded with FeN particles prepared in Example 1 tested by a Japanese JEM-F200 transmission electron microscope (TEM).

[0031] Figure 5 This is the specific surface area data of the porous carbon cathode material loaded with FeN particles prepared in Example 1 tested by the American Quantachrome autosorb iQ gas adsorption instrument.

[0032] Figure 6 It is the cyclic voltammetry curve result of the neutral water system zinc-air / iodine hybrid battery prepared in Example 1 tested by Shanghai Chenhua Company's CHI 760E electrochemical workstation.

[0033] Figure 7 The charge and discharge performance results of the neutral aqueous zinc-air / iodine hybrid battery prepared in Example 1 were tested by Shanghai Chenhua Company's CHI 760E electrochemical workstation.

[0034] Figure 8 It is the specific capacity performance result of the neutral aqueous zinc-air / iodine hybrid battery prepared in Example 1 tested by Shanghai Chenhua Company's CHI 760E electrochemical workstation.

[0035] Fig. 9 It is the cycling performance result of the neutral aqueous zinc-air / iodine hybrid battery prepared in Example 1 tested by Shanghai Chenhua Company's CHI 760E electrochemical workstation.

[0036] Fig.10 It is the cycle performance result of the alkaline zinc-air / iodine hybrid battery prepared in Comparative Example 1 tested by Shanghai Chenhua Company's CHI 760E electrochemical workstation. DETAILED DESCRIPTION

[0037] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0038] like Figure 1 , which is a diagram of the working mechanism of the zinc-iodine battery in an embodiment of the neutral aqueous zinc-air / iodine hybrid battery provided by the present invention.

[0039] Example 1

[0040] The preparation method of the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment is as follows: 1M potassium iodide (KI) as an iodine source and 1M potassium acetate (CH3COOK) as a conductive additive are added to a 1M zinc acetate ((CH3COO)2Zn) aqueous solution, and the neutral zinc-air / iodine hybrid battery electrolyte is uniformly prepared by ultrasonic dispersion at room temperature.

[0041] The preparation method of the positive electrode material of the neutral water system zinc-air / iodine hybrid battery provided in this embodiment is as follows: a porous carbon positive electrode material loaded with FeN particles is obtained by high-temperature calcination of a metal organic framework formed by bimetallic (Fe, Zn) and aminoantipyrine. The specific preparation method is as follows:

[0042] (1) Synthesis of silica nanospheres

[0043] Typically, anhydrous ethanol (75 ml), deionized water (15 ml) and tetraethoxysilane (2 ml) were uniformly mixed. Subsequently, 3 ml of aqueous ammonia was added dropwise to the above solution. The mixture was further centrifuged at 700 rpm, washed and dried to obtain silica nanospheres.

[0044] (2) Synthesis of porous carbon loaded with FeN particles

[0045] 0.3 g of silica nanospheres, 0.6 g of 4-aminoantipyrine, 0.1 g of iron nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.3 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dispersed in a beaker containing 25 ml of methanol. The mixture was stirred evenly at 80°C until the methanol was completely evaporated. After that, the solid powder was heated to 900°C in an inert nitrogen atmosphere and maintained for 1 hour. 3M potassium hydroxide (KOH) solution was used for washing at 80°C for 24 hours to remove silica. Finally, the product was centrifuged and washed with ethanol, and heated to 800°C at a heating rate of 5°C / min in an argon atmosphere and heat treated for 2 hours. After the tubular furnace cooled naturally, the final product, a porous carbon positive electrode material loaded with FeN particles, was obtained.

[0046] The results of the electron scanning microscope (SEM) and X-ray diffraction (XRD) test in this embodiment show that: Figure 2 As shown in Figure 2, the prepared cathode material shows a porous structure. Figure 3 As shown, the horizontal axis X is the diffraction angle (2θ), the vertical axis Y is the relative diffraction intensity, and the diffraction peak corresponds to FeN 0.0324 The physical phase.

[0047] In addition, transmission scanning electron microscopy (TEM) images such as Figure 4 As shown in Figure 1, it can be found that the particle size of FeN particles is 20-50 nm. The nitrogen adsorption-desorption curve is shown in Figure 1. Figure 5 As shown, it is further proved that the pore size of porous carbon is 0.5–10 nm and the surface area is 522 m 2 g –1 .

[0048] The assembly method of the neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment is:

[0049] The positive electrode material, polytetrafluoroethylene and conductive carbon black are weighed, ground evenly in a mass ratio of 8:1:1, and N-methylpyrrolidine is added to obtain a slurry, and then the slurry is evenly coated on a foam nickel current collector, and dried at 80° C. to obtain the neutral aqueous zinc-air / iodine hybrid battery air positive electrode.

[0050] The battery positive electrode and the zinc sheet negative electrode are fixed in the organic glass mold respectively, the catalyst air positive electrode and the zinc sheet negative electrode are separated by a rubber ring, and 6 mol / ml of the above neutral aqueous electrolyte solution is injected into the organic glass mold to obtain a neutral aqueous zinc-air / iodine hybrid battery.

[0051] The cyclic voltammetry curve and charge-discharge performance test results of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example are shown in Figure 6 and Figure 7 Its charge and discharge functions are normal, and the maximum power density is 33mW / cm 2 , indicating that the neutral aqueous zinc-air / iodine hybrid battery prepared in this example has a higher energy conversion efficiency.

[0052] The specific capacity of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is as follows: Figure 8 As shown, at a current density of 5 mA / cm 2 Under constant current discharge conditions, the battery specific capacity is 665mAh / g.

[0053] The cycle performance of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is as follows: Fig. 9 As shown, after working continuously for 1900 hours, the battery performance remains stable. The neutral aqueous zinc-air / iodine hybrid battery prepared by the method of the present invention has good battery cycle stability.

[0054] Example 2

[0055] Different from Example 1, the preparation method of the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment is as follows: 0.5M potassium iodide (KI) and 0.5M sodium iodide (NaI) as iodine sources and 0.5M potassium acetate (CH3COOK) and 0.5M sodium acetate (CH3COONa) as conductive additives are added to a 1M zinc acetate ((CH3COO)2Zn) aqueous solution, and the neutral zinc-air / iodine hybrid battery electrolyte is uniformly prepared by ultrasonic dispersion at room temperature.

[0056] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 24 mW / cm 2 , at a current density of 5 mA / cm 2 Under the condition of constant current discharge, the battery capacity is 520mAh / g. At the same time, the battery performance remains stable after working continuously for 1000 hours.

[0057] Example 3

[0058] Different from Example 1, the preparation method of the positive electrode material of the aqueous zinc-air / iodine hybrid battery provided in this example is as follows: a porous carbon positive electrode material loaded with FeN particles is obtained by high-temperature calcination of a metal organic framework formed by bimetallic (Fe, Zn) and aminoantipyrine. The specific preparation method is as follows:

[0059] (1) Synthesis of silica nanospheres

[0060] Typically, anhydrous ethanol (75 ml), deionized water (15 ml) and tetraethoxysilane (2 ml) were uniformly mixed. Subsequently, 3 ml of aqueous ammonia was added dropwise to the above solution. The mixture was further centrifuged at 700 rpm, washed and dried to obtain silica nanospheres.

[0061] (2) Synthesis of porous carbon loaded with FeN particles

[0062] 0.3 g of silica nanospheres, 0.6 g of 4-aminoantipyrine, 0.1 g of iron nitrate nonahydrate (Fe(NO3)3·9H2O) and 0.3 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dispersed in a beaker containing 25 ml of methanol. The mixture was stirred evenly at 80°C until the methanol was completely evaporated. After that, the solid powder was heated to 700°C in an inert nitrogen atmosphere and maintained for 1 hour. 3M potassium hydroxide (KOH) solution was used for washing at 80°C for 24 hours to remove silica. Finally, the product was centrifuged and washed with ethanol, and heated to 800°C at a heating rate of 5°C / min in an argon atmosphere and heat treated for 2 hours. After the tubular furnace cooled naturally, the final product, a porous carbon positive electrode material loaded with FeN particles, was obtained.

[0063] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 26 mW / cm 2 , at a current density of 5 mA / cm 2 Under the condition of constant current discharge, the battery capacity is 558mAh / g. At the same time, the battery performance remains stable after 500 hours of continuous operation.

[0064] Example 4

[0065] Different from Example 2, in the method for preparing the electrolyte of a neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment, the formula of the neutral zinc-air / iodine hybrid battery electrolyte is:

[0066] Different from Example 1, the preparation method of the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this example is as follows: 2M potassium iodide (KI) as an iodine source and 1M potassium acetate (CH3COOK) as a conductive additive are added to a 3M zinc acetate ((CH3COO)2Zn) aqueous solution, and the neutral zinc-air / iodine hybrid battery electrolyte is uniformly prepared by ultrasonic dispersion at room temperature.

[0067] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 24 mW / cm 2 , at a current density of 5 mA / cm 2 The battery performance remains stable after working continuously for 950 hours under constant current discharge conditions.

[0068] Example 5

[0069] Different from Example 2, in the method for preparing the electrolyte of a neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment, the formula of the neutral zinc-air / iodine hybrid battery electrolyte is:

[0070] Different from Example 1, the preparation method of the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this embodiment is as follows: 0.5M potassium iodide (KI) and 0.5M sodium iodide (NaI) as iodine sources and 0.5M potassium acetate (CH3COOK) as a conductive additive are added to a 0.5M zinc acetate ((CH3COO)2Zn) aqueous solution, and a neutral zinc-air / iodine hybrid battery electrolyte is prepared by ultrasonic dispersion at room temperature.

[0071] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 10 mW / cm 2 , at a current density of 5 mA / cm 2 The battery performance remains stable after working continuously for 720 hours under constant current discharge conditions.

[0072] Example 6

[0073] Different from Example 3, in the method for preparing the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this example, the solid powder is heated to 600° C. in an inert nitrogen atmosphere and maintained for 1 hour.

[0074] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 12 mW / cm 2 , at a current density of 5 mA / cm 2 The battery performance remains stable after working continuously for 720 hours under constant current discharge conditions.

[0075] Example 7

[0076] Different from Example 3, in the method for preparing the electrolyte of the neutral aqueous zinc-air / iodine hybrid battery provided in this example, the solid powder is heated to 1000° C. in an inert nitrogen atmosphere and maintained for 1 hour.

[0077] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 18 mW / cm 2 , at a current density of 5 mA / cm 2 The battery performance remains stable after working continuously for 1120 hours under constant current discharge conditions.

[0078] Example 8

[0079] The positive electrode material of the battery assembly provided in this embodiment uses a commercial mixed catalyst of platinum carbon and ruthenium oxide, and the rest of the electrolyte and the preparation process are the same as those in Example 1.

[0080] The maximum power density of the neutral aqueous zinc-air / iodine hybrid battery prepared in this example is 12 mW / cm 2 , at a current density of 5 mA / cm 2 The battery performance remained stable after continuous operation for 1280 hours under constant current discharge conditions. This proves that the neutral electrolyte invented in this experiment can provide reversible circulation of iodine species, so that the assembled neutral aqueous zinc-air / iodine hybrid battery has good cycle stability.

[0081] Comparative Example 1

[0082] This comparative example uses an alkaline electrolyte of 6M potassium hydroxide plus 1M potassium iodide, and the remaining battery assembly materials and preparation process are the same as those in Example 1. After the battery is assembled, the current is 5mA / cm 2 The cycling performance was tested at a current density of .

[0083] Fig.10 This is a cycle charge and discharge performance diagram of the alkaline zinc-air / iodine hybrid battery assembled in Example 1 with an alkaline electrolyte. In an alkaline electrolyte, the iodine element produced during the charging process will undergo a spontaneous disproportionation reaction to generate iodate ions that are difficult to reduce, resulting in the iodine species being unable to be recycled in the battery. Therefore, the cycle time of the alkaline zinc-air / iodine hybrid battery is only 58 hours.

[0084] The above results show that the neutral aqueous zinc-air / iodine hybrid battery prepared by the method of the present invention has good specific capacity and excellent cycle stability. The present invention promotes the research on neutral rechargeable zinc-air batteries, which plays a certain role in promoting the development of high-performance new energy batteries.

Claims

1. An electrolyte for a neutral aqueous zinc-air / iodine hybrid battery, characterized in that: The electrolyte is a neutral electrolyte, comprising a zinc source, an iodine source and a conductive additive.

2. The electrolyte of the neutral aqueous zinc-air / iodine hybrid battery according to claim 1, characterized in that: The zinc source is from one of zinc sulfate, zinc acetate or zinc oxide.

3. The electrolyte of the neutral aqueous zinc-air / iodine hybrid battery according to claim 1, characterized in that: The iodine source is selected from one or a combination of at least two of potassium iodide, sodium iodide, potassium iodate or elemental iodine.

4. The electrolyte of the neutral aqueous zinc-air / iodine hybrid battery according to claim 1, characterized in that: The conductive additive is selected from one or a combination of at least two of potassium acetate, sodium chloride, potassium chloride, sodium sulfate or potassium sulfate.

5. The electrolyte of the neutral aqueous zinc-air / iodine hybrid battery according to claim 1, characterized in that: The molar concentration of zinc ions in the zinc-air / iodine hybrid battery electrolyte is 0.1M-3M, the molar concentration of iodine ions is 0.1M-3M, and the molar concentration of the conductive additive is 0.1M-3M.

6. A positive electrode for a neutral aqueous zinc-air / iodine hybrid battery, characterized in that: The positive electrode is a porous carbon positive electrode material loaded with FeN particles obtained by calcining a metal organic framework formed by bimetallic (Fe, Zn) and aminoantipyrine at high temperature.

7. The positive electrode of the neutral aqueous zinc-air / iodine hybrid battery according to claim 6, characterized in that: The preparation method of the porous carbon positive electrode material loaded with FeN particles comprises: (1) dispersing 0.1-0.5 g of silica nanospheres, 0.5-1 g of 4-aminoantipyrine, 0.01-0.5 g of ferric nitrate nonahydrate and 0.1-0.5 g of zinc nitrate hexahydrate in methanol, and heating until the methanol evaporates to obtain a solid powder; (2) heating the solid powder to 600-1000° C. in an inert atmosphere and maintaining the temperature for 1-3 hours, and removing the silica nanospheres with an alkaline solution; (3) The product of step (2) is heated to 800-1000° C. and heat treated for 2-4 hours to obtain a porous carbon positive electrode material loaded with FeN particles.

8. The positive electrode of the neutral aqueous zinc-air / iodine hybrid battery according to claim 7, characterized in that: In step (1), the preparation method of the silica nanospheres is as follows: 50 to 100 ml of anhydrous ethanol, 10 to 20 ml of deionized water and 1 to 5 ml of tetraethoxysilane are mixed, 2 to 6 ml of ammonia water is added dropwise, and the silica nanospheres are obtained by centrifugation; in step (2), 1 to 6 M potassium hydroxide solution is used for washing at 80° C. for 24 to 48 hours to remove the silica nanospheres.

9. The positive electrode of the neutral aqueous zinc-air / iodine hybrid battery according to claim 6, characterized in that: In the porous carbon positive electrode material loaded with FeN particles, the loading amount of FeN particles is 0.4-1wt%, the particle size of FeN particles is 20-50nm, the pore size of the porous carbon is 0.5-10nm, and the surface area of ​​the porous carbon is 300-600m 2 g -1 .

10. A neutral aqueous zinc-air / iodine hybrid battery, characterized in that: The battery comprises the electrolyte described in any one of claims 1 to 5 and the porous carbon positive electrode material loaded with FeN particles described in any one of claims 6 to 9.